Investigating In Situ Properties of Recycled Asphalt Pavement with Foamed Asphalt as Base Stabilizer - Christina Plati; Andreas Loizos; Vasilis Papavasiliou; Antonis Kaltsounis (Advances in Civil Engineering)
The objective of the present study was to conduct a comprehensive field experiment for the in situ assessment of in-depth recycled asphalt pavement using foamed asphalt as a stabilization treatment for base works. For this purpose Nondestructive Testing (NDT) data collected using the Falling Weight Deflectometer (FWD) and Ground Penetrating Radar (GPR) along a foamed asphalt recycled pavement section was thoroughly analysed. Critical issues including the stabilized material curing and the contribution of the asphalt layers to the structural properties of the in-depth recycled pavement are discussed. In addition, recommendations concerning the improvement of the structural condition of the in-depth recycled pavement are developed based on this practical approach of investigation using NDT.